Child Poverty in Perspective - UNICEF Innocenti Research Centre (United Nations, 2007)
This Report Card provides a comprehensive assessment of the lives and well-being of children and young people in 21 nations of the industrialized world. Its purpose is to encourage monitoring, to permit comparison, and to stimulate the discussion and development of policies to improve children’s lives. It is the seventh in a series of Innocenti Report Cards, designed to monitor and compare the performance of the OECD countries in securing the rights of their children.